Teaching Street Law in Corrections. Clinical Program Handbook - Georgetown Univ., Washington, DC. Law Center; Georgetown Univ., Washington, DC. Law Center ([S.l.] : Distributed by ERIC Clearinghouse, 1991)
This pamphlet is designed to aid students of law enforcement as they participate in the "Street Law" seminar that pairs students of law enforcement with residents of correctional institutions. The clinical program allows future law enforcement workers to apply their legal knowledge and skills in confronting legal issues and problems in the correctional facilities. This handbook provides clinical requirements and other information to help guide the year long program. Sections include: (1) "Introduction: A Word of Welcome"; (2) "Program Goals for Law Students"; (3) "Course Requirements"; (4) "Evaluations and Grading"; and (5) "Program Goals for Residents of Correctional Facilities." (EH)
Availability: D.C. Street Law project, Georgetown University Law Center, Clinical Program Center, 111 F Street, NW, Suite 330, Washington, D.C. 20001-2095, 202-662-9615.
ERIC Note: For related document, see SO 027 034.
Practitioners.
Teachers.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Citizenship Education; Civics; Correctional Education; Correctional Institutions; Crime; Criminal Law; Law Enforcement; Law Related Education; Laws; Police Education; Postsecondary Education; Practicums; Street Law; District of Columbia; Guides, Classroom -- Teacher